Paul Simon : a life - Eliot, Marc (Wiley, 2010)
Paul Simon, one of the country's most popular musicians, has been a dynamic creative force for more than half a century. Now New York Times biographer Marc Eliot draws on extensive research and original interviews to trace the incredible life and career of this iconic musician. Along the way Eliot examines Simon's early struggles to succeed as a singer-songwriter, the ups and downs of his decades-long collaboration with Art Garfunkel, his at-times obsessive admiration and competitive drive with Bob Dylan, his musical triumphs such as Still Crazy After All These Years and Graceland, the spectacular failure of his Broadway musical The Capeman, and much more. The first comprehensive biography of Paul Simon and his music Explores the complex relationship between Paul Simon and Art Garfunkel through years of their musical breakups and reunions Reveals personal details, with interviews, of Simon's life away from music Includes dozens of exclusive photographs, several published for the first time.